Ultrasonic Effect on Wood Electroless Ni-P/nano-SiC Composite Coatings - Pan, Yanfei; Huang, Jintian; Guo, Tongcheng; Zhang, Shaobo (Asian Journal of Chemistry, 2014)
In this study, the particle size, wear resistance of coatings and the dispersibility of nano-SiC (size of 40 nm) by ultrasonic dealing with the plating solution to disperse nano-SiC particles were investigated. The crystalline and amorphous characteristics of the composite coatings was analyzed by X-Ray diffraction, surface morphology and element composition were investigated by scanning electron microscope equipped with energy diffraction spectrum. The wear resistance of coatings was measured using the rolling wear testing machine, indicating that the wear resistance increased by 50 % comparing with SiC free electroless Ni coating. The results showed that ultrasonic can decrease the particle size of wood surface coatings. Furthermore, ultrasonic had a significant effect on nano-SiC dispersibility and the structure of coatings maintained as nano-SiC particles embedded. Besides, the particles of wood surface coatings dispersed more homogeneous with the ultrasonic power up to 720 w, which promoted the Ni-P and nano-SiC particles distribution more compact.